Sistem Informasi Eksekutif Pertumbuhan UMKM Berbasis Dashboard RealTime di Kota Lubuklinggau - Yogi Primadasa; Arie Yandi Saputra; Yayang Eluis Bali Mawartika; Syafiul Hamidani (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2026)
This research discusses the development and implementation of a real-time dashboard-based executive information system for monitoring the growth of Micro, Small, and Medium Enterprises (MSMEs) in Lubuklinggau City. The main focus of this study is on the adaptation of information technology supporting the executive information system (EIS), the real-time interactivity of the dashboard, and the integration of internal and external data for MSMEs. The information technology used in the development of the EIS is designed with characteristics such as scalability, adaptability to global trends, and efficiency in processing big data to support strategic decision-making. This approach aims to provide a flexible and relevant solution for managing MSME performance in the digital era. Analysis of the impact of the dashboard implementation shows a significant increase in MSME productivity after the system is implemented. Comparison of performance before and after implementation provides empirical evidence that the system is able to improve operational efficiency and drive business growth. Overall, this report emphasizes the importance of utilizing modern information technology to address the challenges faced by MSMEs, while providing data-driven solutions that support local economic development in Lubuklinggau.